List of referees for year 2016 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2016)
All submitted manuscripts relevant to the journal’s profile are reviewed. All referees are eminent experts in relevant fields, with papers published in these fields in the last three years. Editorial Board applies the iThenticate (CrossRef and CrossCheck) service for verifying the originality of submitted papers and for preventing duplicate publishing and plagiarism. Journal applies a „double blind peer review process“ for papers. Authors and reviewers are anonymous to each other in the process of review. Reviews after the article has been published are allowed and encouraged for subsequent evaluation of papers and authors. A peer reviewer assists the editor in making editorial decisions and through the editorial communications with the author may also assist the author in improving the paper.